Extraction of value-added chemicals from biorefinery residues - Liu, Yanguang (Kansas State University, 2015)
Large quantities of byproducts are generated during the biomass processing, which leads to under-utilization of resources and concomitant waste disposal problem. Typically, these byproducts still contain considerable amounts of high-value compounds that have important industrial applications. However, in current time, most of these byproducts are used for low-value applications, including as boiler fuel. These byproducts are potential sources for many valuable chemicals such as antioxidants, flavors, colorants, preservatives, and biocides. Therefore, the reuse and recycle of these biomass residues is very important for the bioeconomy. By some additional and necessary processing steps, we can transfer those biomass residues from a low-value level to a higher value status and apply the final products to various fields such as food industry, and pharmaceutical industry, etc. Till date, limited research has been reported in the production of important specialty chemicals from biomass residues. This thesis is focused on the solvent extraction and isolation of valuable chemicals from bioprocessing byproducts. While choosing different solvents and techniques, “environmental friendly” green solvents were also evaluated. Also some new techniques, such as thin-layer chromatography plates making and laboratory-made lignin are developed to make the research more economically feasible. Even though conventional extraction method such as solid-liquid extraction was evaluated, we tried to minimize the solvent/biomass ratio and also augmented additional processes to the conventional process to obtain higher yield of compounds of interest (COI). In this research, different biomass resources were evaluated for valuable specialty chemicals. These resources include: lignocellulosic biomass and raw biomass. Lignocellulosic biomass is a sustainable feedstock for the production of biofuels and chemicals. The potential chemicals from the resources were extracted using various organic solvents and analyzed by gas chromatography-mass spectrometry (GC-MS). The results indicated that the selected biomass residues contain relatively higher amounts of three valuable compounds: vanillin, apocynin, and phytol. Different types of organic solvents and extraction techniques were tested to optimize the extraction process. Ultra-sonication was considered as an efficient extraction method and ethanol was chosen as the final solvent. Commercially viable isolation methods such as thin-layer chromatography (TLC) and column chromatography were also studied in this research. A solvent system of hexane, dichloromethane, ethyl acetate, and chloroform with 1:1:1:0.1 v/v ratio gave us a good separation of the COI. Biomass-derived lignin was made in the laboratory to compare with commercially available lignin. The results show that the laboratory-made lignin contains similar bioactive compounds and gives us a good quantity of target compounds. In conclusion, instead of letting the byproducts being discarded or used as low-value applications or become a threat to the environment, the decision to select them as raw materials to produce valuable specialty targeted compounds for industries has been demonstrated in our research. The future research will focus on optimization and scale-up study of the extraction process. In addition, the application and production of bioactive compounds will be further evaluated.
Keywords: Extraction; value-added chemicals; biorefinery; Agriculture, General (0473); Chemistry (0485)